Glomerulopathy Associated With Moderate Obesity - Yusuke Okabayashi; Nobuo Tsuboi; Takaya Sasaki; Kotaro Haruhara; Go Kanzaki; Kentaro Koike; Yoichi Miyazaki; Tetsuya Kawamura; Makoto Ogura; Takashi Yokoo (Kidney International Reports, 2016)
Obesity-related glomerulopathy is an established secondary glomerular disease that may occur in obese individuals with a body mass index (BMI) of ≥30 kg/m2. However, patients with moderate obesity (BMI ≤ 30 kg/m2) may also develop this disease. Methods: A total of 20 patients with grade 1 obesity (25 ≤ BMI < 30 kg/m2) with persistent proteinuria, without evidence of other renal diseases, were analyzed retrospectively. These patients were compared with 20 patients with grade 2 or higher obesity (BMI ≥ 30 kg/m2) with persistent proteinuria. Biopsies of 31 kidney transplant donors as healthy controls were used to compare histologic parameters. Results: Similar to the grade 2 or higher obesity group, the grade 1 obesity group had a male predominance (85%) and showed a high incidence of hypertension (80%). Urinary protein excretion and renal outcome parameters were comparable between the groups. Patients with grade 1 obesity showed typical histologic features of obesity-related glomerulopathy: low glomerular density with glomerulomegaly. The glomerular density and mean glomerular volume in the grade 1 group, the grade 2 or higher group, and the kidney transplant donors with grade 1 obesity were 1.6 ± 0.8 versus 1.4 ± 0.6 versus 3.0 ± 1.1 (per mm2) and 6.1 ± 2.1 versus 6.4 ± 1.6 versus 2.9 ± 0.8 (×106 μm3), respectively. Discussion: A glomerulopathy similar to obesity-related glomerulopathy can occur in moderately obese individuals. Renal factor(s), such as low glomerular density, may thus underlie susceptibility to this disease entity as well as BMI.